Real Time Locating Systems for Human Centered Production Planning and Monitoring. Issue 2 (2022) - Wolf, M.; Rantschl, M.; Auberger, E.; Preising, H.; Sbaragli, A.; Pilati, F.; Ramsauer, C.
Abstract: Production companies often operate in a dynamic and volatile environment. This leads to an increasing demand for continuous changes in their production systems and processes. Furthermore, decreasing product life cycle times and rising market demand for product variety and individualized products is bringing about the necessity for the monitoring and coordination of processes in the operations phase. As a result of these developments production management is facing new challenges in decision making for the optimal settings of the production system design and the related coordination of production. All of this demands enormous efforts to maintain a consistent and reliable database for the ongoing configuration and coordination of the production system. It is thus a remarkable challenge for industrial companies. Real time locating systems (RTLS) with their ability to continuously monitor the current position and parameters (speed, direction, etc.) of process resources (operators, equipment, products, etc.) offer several potential benefits for the manufacturing industry. The potential areas of application can be identified in different layers of production management. They range from data acquisition on shop floor level through reconfiguration of production systems to providing real time feedback for the blue collars. Furthermore, it allows dynamic coordination of production orders for industrial plants via appropriate digital twin (DT) technologies. This paper proposes an original framework for RTLS in industrial environments and presents a case study for framework application at the TU Graz Learning Factory.